ChemInform Abstract: Diastereodivergent Organocatalysis for the Asymmetric Synthesis of Chiral Annulated Furans. Issue 43 (October 2015) - Verrier, Charlie; Melchiorre, Paolo
Abstract Chiral 2, 3‐furan fused carbocycles bearing adjacent quarternary and tertiary carbon stereocenters are selectively synthesized by asymmetric addition of β‐ketoesters to 2‐(1‐alkynyl)‐2‐alkene‐1‐ones catalyzed by natural cinchona alkaloids followed by a silver‐catalyzed intramolecular cycloisomerization.